Carbon-encapsulated V2O3 nanorods for high-performance aqueous Zn-ion batteries - Hao, Ziyi; Jiang, Weikang; Zhu, Kaiyue (Frontiers in Chemistry, 2022)
Searching for stable cathodes is of paramount importance to the commercial development of low-cost and safe aqueous Zn-ion batteries (AZIBs). V2O3 is a good candidate for AZIB cathode but suffer from unsatisfied cycling stability. Herein, we solve the stability issue of V2O3 cathode through coating a robust carbon shell. Strong evidence was provided that V2O3 was oxidized to favorable V2O5·nH2O during charging and the carbon shell could promote the oxidation of V2O3 to V2O5·nH2O. The discharge capacity was increased from 45 mAh g-1 to 336 mAh g-1 after V2O3 was oxidized to V2O5·nH2O, indicating the higher Zn2+-storage capability of V2O5·nH2O than V2O3. In addition, the rate-capability and long-term cycling performance are greatly enhanced after coating carbon shell on the surface of V2O3 nanorods. Therefore, presented strategy of introducing carbon shell and fundamental insights on the favorable role of carbon shell in this study contribute to the advancement of high stable AZIBs.